Relación entre el capital humano y el producto en Ecuador: El rol de las políticas educativas - Elita Mora; Irene Vicente; Patricia Villegas; Rafael Alvarado (Atlantic Review of Economics, 2017)
– The objective of this research is to examine the relationship between human capital and output in Ecuador through cointegration techniques. We use data compiled by the World Bank in the World Development Indicators (2017) and by Barro and Lee (2013) of the period 1982-2015. Despite the instability of education policies in this country, the results are consistent with the approach of the endogenous growth model developed by Lucas (1988). We find that human capital measured by literacy rate, and physical capital measured by gross fixed capital formation, have a stable long-term and short-term relationship with output in this country. Finally, we find that there is a unidirectional Granger (1988) causality from human capital to output and from human capital to physical capital. One implication of economic policy derived from this research is that an increase in investment in the labor force endowments can increase output and physical capital.
Keywords: E23; E22; J24; 330; Human capital; Physical capital; Output; Time series; Ecuador